2015
DOI: 10.7124/bc.0008c7
|View full text |Cite
|
Sign up to set email alerts
|

mTOR signaling and its involvement in the regulation of cell movements through remodeling the cytoskeleton architecture

Abstract: mTOR kinase is one of the basic links at the crossroad of several signal transduction pathways. De re gulated mTOR kinase signaling accompanies the progress of cancer, diabetes, neurodegenerative disorders and aging. Implication of mTOR inhibitor rapamycin decreases migration and invasion of malignant cells, and metastasis formation. However, a precise mechanism of the regulation of cellular locomotion by mTOR kinase is not fully understood. This article focuses on the recent fi ndings that demonstrated a poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The mTOR signaling pathway senses nutrient availability and can switch on autophagy during times of nutrient stress [ 40 ]. This pathway also integrates information about cellular nutrient and energy status with cytoskeletal dynamics, remodeling the actin cytoskeleton to facilitate invasion and metastasis [ 41 , 42 ]. Our data suggest that autophagy and the remodeling of cytoskeleton dynamics is playing a role in antifolate drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The mTOR signaling pathway senses nutrient availability and can switch on autophagy during times of nutrient stress [ 40 ]. This pathway also integrates information about cellular nutrient and energy status with cytoskeletal dynamics, remodeling the actin cytoskeleton to facilitate invasion and metastasis [ 41 , 42 ]. Our data suggest that autophagy and the remodeling of cytoskeleton dynamics is playing a role in antifolate drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Serine 2481 localizes at the regulatory domain of the kinase and could be involved in the modulation of its activity [8,9]. In mammalian cells mTOR exists as a core enzyme of two different complexes: mTORC1 and mTORC2 [13,14,15]. Earlier studies showed that specific mTOR inhibitor rapamycin treatment did not affect Serine 2481 phosphorilation.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 localization is well characterized in mammalian cells. Newest data demonstrate a wide distribution of mTORC1 in the plasma membrane, cytosol, lysosome and the nucleus although in some cases the evidence is questionable [21][22][23]. In contrast to mTORC1, the mTORC2 localization is more obscure.…”
Section: Discussionmentioning
confidence: 99%